Efficacy and safety of Xian-Lian-Jie-Du optimization decoction as an adjuvant treatment for prevention of recurrence in patients with stage IIIB/IIIC colon cancer: study protocol for a multicentre, randomized controlled trial - Xuechen Geng; Ziqiang Wang; Li Feng; Yanhong Gu; Renjie Wang; Qinghua Yao; Yangxian Xu; Jianyu Wu; Zhiwei Jiang; Kai Chen; Wenwei Hu; Dongxin Tang; et al. (BMC Complementary Medicine and Therapies, 2023)
Abstract Introduction Colon cancer remains one of the most prevalent cancers worldwide. Unfortunately, there are no recognized and effective therapeutic strategies to prevent tumor recurrence after radical resection and chemotherapy, and the disease-free survival (DFS) in patients with stage IIIB or IIIC disease remains unsatisfactory. Xian-Lian-Jie-Du optimization decoction (XLJDOD) is a Chinese herbal medicine (CHM) empirical prescription, which has been validated experimentally and clinically that could inhibit the progression of colorectal cancer and ameliorate the symptoms. The purpose of this study is to evaluate the efficacy and safety of XLJDOD in prevention of recurrence of colon cancer. Methods This study is a multi-center, double-blind, randomized, placebo-controlled trial conducted at 13 hospitals of China. Following the completion of surgery and adjuvant 5- fluorouracil-based chemotherapy, a total of 730 subjects with stage IIIB or IIIC colon cancer will be randomized in a 1:1 ratio to an intervention group (n = 365; XLJDOD compound granule) and a control group (n = 365; Placebo). Patients will receive 6-month treatments and be followed up with 3 monthly assessments for 2 years. The primary outcome is 2-year DFS rate and the secondary outcomes are 1, 2-year relapse rate (RR), overall survival (OS) and quality of life (QoL). Safety outcomes such as adverse events will be also assessed. A small number of subgroup analysis will be carried out to explore the heterogeneity of effects of XLJDOD. Discussion The outcomes from this randomized controlled trial will provide objective evidences to evaluate XLJDOD’s role as an adjuvant treatment in colon cancer. Trial registration www.ClinicalTrials.gov , identifier: NCT05709249. Registered on 31 Jan 2023.